Isolation and characterization of rhizobia and evaluation of their effect on radish (Raphanus Sativus ) growth (Bangladesh Journal of Botany, 2024)
This study focused on isolating and characterizing rhizobia from alfalfa root nodules and assessing their impact on Radish (Raphanus sativus L) growth. Fifteen isolates underwent morphological and biochemical analyses, revealing consistent traits with variations in colony elevation. Confirmatory tests identified all isolates as gram-negative, rod-shaped, catalase, and oxidase positive. Notably, 13 isolates exhibited citrate positivity, 14 urease positivity, and 2 gelatinase positivity. Ten isolates produced indole-3-acetic acid, nine solubilized phosphate, and all produced ammonia. R12 displayed the highest seed germination (100%). Significant effects (P < 0.05) on radish growth were observed, with R37 yielding the highest values for root length (19 cm), R5 for shoot length (9 cm), R5 for leaf number (12.6), R36 for fresh weight (8 g), and R37 for dry weight (5 g). These superior isolates hold potential as biofertilizers for enhancing radish growth.Bangladesh J. Bot. 53(1): 185-192, 2024 (March)